A phenotypic marker for quantifying heat stress impact during microsporogenesis in rice (Oryza sativa L.) - Jagadish, Krishna S.V.; Craufurd, Peter; Shi, Wanju; Oane, Rowena (Commonwealth Scientific and Industrial Research Organisation, 2014)
Gametogenesis in rice (Oryza sativa L.), and particularly male gametogenesis, is a critical developmental stage affected by different abiotic stresses. Research on this stage is limited, as flowering stage has been the major focus for research to date. Our main objective was to identify a phenotypic marker for male gametogenesis and the duration of exposure needed to quantify the impact of heat stress at this stage. Spikelet size coinciding with microsporogenesis was identified using parafilm sectioning, and the panicle (spikelet) growth rate was established. The environmental stability of the marker was ascertained with different nitrogen (75 and 125 kg ha–1) and night temperature (22°C and 28°C) combinations under field conditions. A distance of –8 to –9 cm between the collar of the last fully opened leaf and the flag leaf collar, which was yet to emerge was identified as the environmentally stable phenotypic marker. Heat stress (38°C) imposed using the identified marker induced 8–63% spikelet sterility across seven genetically diverse rice genotypes. Identifying the right stage based on the marker information and imposing 6 consecutive days of heat stress ensures that >95% of the spikelets in a panicle are stressed spanning across the entire microsporogenesis stage.